Visual disturbances before and after transnasal endoscopic surgery for craniopharyngiomas (Ukrainian Journal of Ophthalmology, 2025)
Background: Craniopharyngiomas (CP) are benign epithelial tumors of the chiasmal and sellar region and/or the third ventricle region which arise from embryonic remnants of Rathke’s pouch. They are in close proximity to the surrounding nervous, endocrine and vascular structures of the brain such as the chiasm, optic nerves and tracts, hypothalamus, pituitary stalk, major vessels and their branches, including perforating branches of the anterior cerebral, posterior communicating, and posterior cerebral arteries. Tumor relation to the optic tracts is an important aspect of surgery for CP. The blood supply to the optic nerve/chiasm complex is usually not affected, which allows maintaining it perioperatively; however, sometimes in radical surgery for CP there is elimination of some perforating arteries from the blood supply and devascularization of the chiasm, causing ischemic abnormalities in the chiasm.Purpose: To determine the features of visual disturbances before and after surgery for craniopharyngioma.Material and Methods: We examined the medical records of a cohort of 61 patients who underwent treatment including transnasal endoscopic surgery for suprasellar craniopharyngioma at the Transsphenoidal Neurosurgery Department, Romodanov Neurosurgery Institute, during the period from 2017 through 2020. The main group included 48 patients (96 eyes). Of these, 46 patients had presented with visual disturbances (reduced visual acuity and/or visual field defects), and 2 patients exhibited them after, but not before surgery. Patients underwent clinical and neurological, eye, and otoneurological examination.Results: Visual disturbances in the presence of suprasellar craniopharyngiomas were found in 46 patients (75%), and their amount and severity substantially varied, which was associated with mechanical compression of the chiasm, growth of the tumor into the optic nerve and chiasm, as well as impaired chiasmal blood supply. The pupillomacular bundle and optic tracts are involved in exerting an effect on the posterior chiasm in suprasellar CP, which was reflected by the predominance of the symmetric chiasmal syndrome (39.1%) with bilateral optic atrophy, and accompanied by reduced visual acuity (78.3%), visual field defects (96.7%), bitemporal heteronymous hemianopia with central scotoma (27.2%), bitemporal paracentral scotoma (22.8%) and homonymous hemianopia (6.5%). The surgical treatment resulted in improvement or restoration of visual functions in 58.3% of patients. Postoperative worsening of visual functions was observed not only in patients who did exhibit visual disturbances preoperative (16.6%) but also in those who did not (4.2%), which was due to devascularization of the chiasm in radical surgery for CP.Conclusion: Transnasal endoscopic surgery for CP enables direct visualization and surgical control of the vessels supplying the chiasm. In addition, this approach allows performing a rather radical surgery with as low as 20.8% postoperative frequency of visual loss or appearance of visual disturbances.
Keywords: skull-base tumors; craniopharyngioma; chiasmal syndrome; compressive optic neuropathy; chiasmal blood supply; devascularization of the chiasm; transnasal endoscopic surgery